Porous natural graphite brush material and preparation method and application thereof
By using porous natural graphite brush materials, using the combination of natural graphite powder, D374 composite powder, medium temperature bitumen powder, melamine and SiC powder, combined with plasticizer and baking treatment, the existing brush materials have high resistance, poor wear resistance, poor high temperature resistance and high friction coefficient in high rotation speed, high linear speed, and high current environments, and have achieved low resistivity, high flexural strength, small friction coefficient and high temperature resistance. It is suitable for generator sets above 300 MW.
Patent Information
- Application Number
- CN202510354271.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-25
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2045-03-25
AI Technical Summary
The existing brush materials exhibit high resistance, poor wear resistance, poor high temperature resistance and high friction coefficient in use environments with high rotation speed, high linear speed and high current, and cannot meet the needs of generator sets above 300 MW.
Porous natural graphite brush material is used, and the preparation method includes mixing natural graphite powder, D374 composite powder, medium temperature bitumen powder, melamine and SiC powder, adding plasticizer, and calcining to form a material with connecting pores.
It achieves low resistivity, high flexural strength, small friction coefficient and high temperature resistance. It is suitable for excitation system collector ring brushes of large and medium-sized steam turbine generator sets of more than 300 MW, which can reduce the "air cushion" phenomenon during high-speed operation and reduce the occurrence of arcs and sparks.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of electric brushes, and in particular relates to a porous natural graphite electric brush material and a preparation method and application thereof. Background Art
[0002] The brush is an important component of the motor, responsible for conducting current between the rotating parts and the stationary parts. Because it is mostly made of graphite, it is also called a carbon brush. The process is basically to coat graphite powder, including various artificial graphite powders, with asphalt or artificial resin binder. In this way, the formability of the graphite powder material is improved. After pressing, curing and other processes, a brush material with a certain strength, resistivity and service life is produced.
[0003] However, traditional raw materials and process methods have many limitations and are difficult to meet the requirements of some high-end motors. For example, using too much artificial graphite powder will lead to too high hardness of the product, increase the friction coefficient, and affect the commutation performance of the brush; using too little artificial resin will result in low strength and poor wear resistance, while too much will result in too high a resistivity, which will easily cause excessive temperature rise during the use of the brush, causing the brush material to deform due to heat and unable to be used normally.
[0004] Chinese invention patent publication number CN108907205A discloses a manufacturing process of a composite material brush, comprising the following steps: S1, raw materials; S2, graphite powder, coke powder, tungsten disulfide powder, and modified coal tar pitch are mixed uniformly in a weight ratio of 1-1.5:1-2:0.2-0.4:0.6-1, and then heated to 120-150°C, and then poured into a granulator to make particles with a particle size of 20-40 mm to obtain base particles; the base particles are placed in a roasting furnace, a protective gas is introduced, and the base particles are heated to 2600-3000°C for 4-6 hours to graphitize them, and then crushed to a particle size of no more than 5 mm particles; S3, preparing working layer raw materials, transition layer raw materials, and welding layer raw materials; S4, laying the working layer raw materials, transition layer raw materials, and welding layer raw materials in a graphite grinder in a thickness ratio of 15-20: 6-8: 3-4, and then introducing argon as a protective gas at 850-950°C and a pressure of 30-45 MPa for hot pressing for 20-30 min to obtain a block material; S5, processing the above block material into a brush substrate.
[0005] Another Chinese invention patent publication number CN106025745A discloses a graphite brush and a preparation method thereof, which is made of the following raw materials in parts by weight: 10-60 parts of graphite, 20-40 parts of asphalt, and 10-30 parts of asphalt-based graphene. The preparation steps are as follows: (1) hot melting, under the protection of nitrogen or inert gas, hot melting the asphalt to obtain a melt, and keeping the temperature constant at 500°C; (2) pyrolysis, heating the melt to 1500°C at a heating rate of 10°C / min, and keeping the temperature constant for 0.1-1 h; (3) grapheneization, heating the melt at 1500°C to 3300°C at a heating rate of 100°C / min, and keeping the temperature constant for 1-3 min; (4) cooling, during the cooling process, the melt is oscillated with ultrasound, and a certain amount of asphalt is added for stirring when the temperature of the melt drops below 400°C; (5) solidification and sintering to obtain a graphite brush blank.
[0006] However, the brushes prepared by the above invention can only meet the use of small generator sets below 100 MW, and cannot meet the use requirements of high speed, high linear speed, and high current of generator sets above 300 MW, and the use performance is unsatisfactory. In view of this, the art urgently needs to provide a brush material with low resistance, wear resistance, high temperature resistance and low friction coefficient. Summary of the invention
[0007] In view of the problems existing in the prior art, the present invention provides a porous natural graphite brush material and a preparation method and application thereof.
[0008] To achieve the above purpose, the technical solution adopted by the present invention is as follows: A method for preparing a porous natural graphite brush material comprises the following steps: (1) Mixing natural graphite powder, D374 composite powder, medium temperature asphalt powder, melamine and SiC powder to obtain dry powder; (2) Add plasticizer to the dry powder, mix, and calcine to obtain the product.
[0009] Preferably, the laser particle size D of the natural graphite powder is 50 =65-90 μm, D 90 =155-180 μm, particle size composition -200 mesh (meaning the undersize after passing through a 200 mesh sieve) accounts for ≥99.0%; fixed carbon content ≥99.5%, ash content ≤0.15%, volatile matter content ≤1.0%, moisture content ≤0.5%, pH value = 5.5-8.0.
[0010] Preferably, the particle size composition of the D374 composite powder is: +160 mesh (indicates the sieve after passing through a 160 mesh sieve) accounts for ≤10%, -320 mesh accounts for 50-55%; ash content is ≤1.5%, and moisture content is ≤1%. The physical and chemical performance indicators of the D374 composite powder sintered material are: resistivity 31-35 μΩ·m, HR 10 / 980 Rockwell hardness value 54-60, Shore hardness value ≥15, flexural strength ≥6 MPa, volume density 1.45-1.52 g / cm 3 .
[0011] Preferably, the medium-temperature asphalt powder has a softening point of ≤100°C, a coking value of 65-69%, an ash content of ≤0.1%, a toluene insoluble content of ≤20%, a moisture content of ≤4.9%, and a volatile matter content of ≤40%.
[0012] The invention ensures that interconnected pores are formed in the porous natural graphite brush material by adding a proper amount of melamine, and the open pore porosity reaches 35-42%.
[0013] Preferably, the laser particle size D of the SiC powder is 50 =3-7 μm, SiC content ≥99.9%, free carbon content ≤0.05%, Fe2O3 content ≤0.02%.
[0014] Preferably, the dry powder is composed of 47-57% natural graphite powder, 14-24% D374 composite powder, 12-18% medium-temperature asphalt powder, 9-15% melamine and SiC powder to make up to 100% by weight.
[0015] More preferably, the dry powder is composed of 51-53% natural graphite powder, 18-20% D374 composite powder, 14-16% medium temperature asphalt powder, 12-15% melamine and SiC powder to 100% by weight.
[0016] Preferably, the mixing process in step (1) includes first stirring at 35-45 rpm for 2-3 h, then heating to 90-110° C. for 1-2 h, and finally cooling.
[0017] The present invention heat mixes dry powders, evaporates the moisture in the powders after heating, increases the air temperature between the powders and in the powders, increases the activity of the powders, and facilitates the flow between the powders. After a certain period of time, multiple powders are fully mixed, and the uniformity of distribution of various powders in the mixture is greatly improved.
[0018] Preferably, the mixing speed in step (2) is 30-50 rpm, the mixing time is 0.5-1.5 h, and after the mixing is completed, it needs to be heated to 90-100° C., dried, cooled and sieved through a 100-200 mesh sieve.
[0019] Preferably, the plasticizer in step (2) includes phenolic resin, epoxy resin, organic solvent and alcohol.
[0020] Preferably, the phenolic resin accounts for 5-10% by weight of the dry powder, the epoxy resin accounts for 5-10% by weight of the dry powder, the organic solvent accounts for 15-35% by weight of the dry powder, and the alcohol accounts for 50-75% by weight of the dry powder.
[0021] Preferably, the organic solvent is acetone.
[0022] The density of phenolic resin is 1.055-1.065 g / cm 3 , resin content 62±4%, free phenol content ≤10%, appearance is reddish brown transparent liquid.
[0023] The softening point of epoxy resin is 22-27°C, the epoxy value is 0.44-0.47 mol / 100 g, and the volatile matter content (100°C×3 h) is ≤1.0%.
[0024] The density of acetone is ≥0.795 g / mL, the content is ≥99.5%, the boiling point is 56±1℃, the evaporation residue is ≤0.001%, the water content is ≤0.1%, and the appearance is a colorless transparent liquid.
[0025] The invention realizes the slurry kneading process by adding a plasticizer, removes the gas between the material powder, reduces the volume of the powder mixture, and improves the kneading efficiency.
[0026] Preferably, the pressing is required before calcination in step (2), the pressing pressure is 10-20 MPa, and the volume density of the pressed green body is 1.3-1.6 g / cm 3 The pressed green sheet has no delamination or cracks, has good strength, and is not easy to fall off corners. It can meet the forming requirements of various specifications of pressed green sheets with a size of less than 200 mm × 200 mm × 50 mm.
[0027] Preferably, the calcination temperature curve includes first heating to 280-320°C, keeping warm for 3-4 h, and a heating rate of 55-65°C / h; then heating to 400-420°C, keeping warm for 3.5-4.5 h, and a heating rate of 3-5°C / h; then heating to 500-540°C, keeping warm for 3.5-4.5 h, and a heating rate of 2-3°C / h; finally heating to 970-990°C, keeping warm for 11-13 h, and a heating rate of 4-15°C / h.
[0028] The invention also provides a porous natural graphite brush material prepared by the above preparation method.
[0029] Preferably, the volume density of the porous natural graphite brush material is 1.25-1.40 g / cm 3 , resistivity ≤27μΩ·m, flexural strength 7-16 MPa, friction coefficient <0.3, HR 10 / 196 Rockwell hardness value 48-78, open porosity 35-42%.
[0030] The present invention also provides the use of the porous natural graphite brush material or the porous natural graphite brush material prepared by the preparation method in brushes.
[0031] Compared with the prior art, the present invention has the following beneficial effects: (1) The present invention provides a porous natural graphite brush material having a volume density of 1.25-1.40 g / cm 3 , resistivity ≤27 μΩ·m, flexural strength 7-16 MPa, friction coefficient <0.3, HR 10 / 196 Rockwell hardness 48-78, open porosity 35-42%, can be used for collector ring brushes in excitation systems of large and medium-sized steam turbine generator sets above 300 MW, the linear speed in the use environment can reach 80 m / s, and the current density is 4-12 A / cm 2 , which has good industrial application prospects.
[0032] (2) The porous natural graphite brush material of the present invention has a soft and fine texture, a uniform pore distribution, and a brush body covered with a large number of interconnected small pores, which can effectively suppress the occurrence of the "air cushion" phenomenon when the generator set is running at high speed, reduce arcs and sparks, and improve the current uniformity of the brush. DETAILED DESCRIPTION
[0033] It is worth noting that the raw materials used in the present invention are all common commercially available products, among which natural graphite powder is purchased from Qingdao Xingguang Graphite Material Co., Ltd.; D374 composite powder is purchased from Harbin Oriental Electric Carbon Factory; phenolic resin, model T209-1A, is purchased from Hebei Zetian Chemical Co., Ltd.; epoxy resin, model WSR6101, is purchased from Nantong Xingchen Synthetic Materials Co., Ltd.; acetone, content ≥99.5%; alcohol, volume content 95%.
[0034] Example 1 A porous natural graphite brush material, the preparation method is as follows: (1) Weigh natural graphite powder (laser particle size D 50 =65-90 μm) 52%, D374 composite powder 19%, medium temperature asphalt powder (softening point 100℃, coking value 65%) 15%, melamine 12% and SiC powder (laser particle size D 50=65-90μm) 2%, stirred at 42 rpm for 3 h in a Z-type mixing pot, mixed, heated to 100°C, kept constant temperature for 2 h, and naturally cooled to below 50°C to obtain dry powder; (2) Add plasticizer to the dry powder (the weight percentage of each component of the plasticizer in the dry powder is: phenolic resin 7.5%, epoxy resin 7.5%, acetone 35% and alcohol 50%), mix at 40 rpm for 1 hour, heat to 100°C, dry, cool naturally, and pass through a 200-mesh sieve. Pour it into a mold for pressing, use a 200-ton hydraulic press, set the pressure to 10 MPa, and press to form the green sheet with a size of 67×117×height H, and a green sheet volume density of 1.5 g / cm 3 The compact was placed in a stainless steel crucible, compressed with fillers, sealed with refractory clay, and placed in a box furnace for roasting. The roasting temperature curve is shown in Table 1. After the roasting, it was naturally cooled to room temperature to obtain the product.
[0035] Table 1 Calcination temperature curve
[0036] Example 2 A porous natural graphite brush material, the preparation method is as follows: (1) Weigh natural graphite powder (laser particle size D 50 =65-90 μm) 47%, D374 composite powder 24%, medium temperature asphalt powder (softening point 100℃, coking value 65%) 15%, melamine 12% and SiC powder (laser particle size D 50 =65-90μm) 2%, stirred at 35 rpm for 3 h in a Z-type mixing pot, mixed, heated to 110℃, kept constant temperature for 1 h, and naturally cooled to below 50℃ to obtain dry powder; (2) Add plasticizer to the dry powder (the weight percentage of each component of the plasticizer in the dry powder is: phenolic resin 5%, epoxy resin 5%, acetone 15% and alcohol 75%), mix at 50 rpm for 0.5 h, heat to 90 ° C, dry, cool naturally, and pass through a 100 mesh sieve. Pour it into the mold for pressing. Use a 200-ton hydraulic press with a pressure setting of 20 MPa to press and form the green compact. The green compact has a size of 67×117×height H and a bulk density of 1.3 g / cm 3 The compact was placed in a stainless steel crucible, compressed with fillers, sealed with refractory clay, and placed in a box furnace for roasting. The roasting temperature curve is shown in Table 1. After the roasting, it was naturally cooled to room temperature to obtain the product.
[0037] Example 3 A porous natural graphite brush material, the preparation method is as follows: (1) Weigh natural graphite powder (laser particle size D50 =65-90 μm) 57%, D374 composite powder 14%, medium temperature asphalt powder (softening point 100℃, coking value 69%) 15%, melamine 12% and SiC powder (laser particle size D 50 =65-90μm) 2%, stirred at 45 rpm for 2 h in a Z-type mixing pot, mixed, heated to 90°C, kept constant temperature for 2 h, and naturally cooled to below 50°C to obtain dry powder; (2) Add plasticizer to the dry powder (the weight percentage of each component of the plasticizer in the dry powder is: phenolic resin 10%, epoxy resin 10%, acetone 25% and alcohol 55%), mix at 30 rpm for 1.5 hours, heat to 100 ° C, dry, cool naturally, and pass through a 200 mesh sieve. Pour it into the mold for pressing, use a 200-ton hydraulic press, set the pressure to 20 MPa, press and form, the green sheet specifications are 67×117×height size H, and the green sheet volume density is 1.6 g / cm 3 The compact was placed in a stainless steel crucible, compressed with fillers, sealed with refractory clay, and placed in a box furnace for roasting. The roasting temperature curve is shown in Table 1. After the roasting, it was naturally cooled to room temperature to obtain the product.
[0038] Example 4 A porous natural graphite brush material, which differs from Example 1 only in the dry powder composition.
[0039] The dry powder consists of the following components by weight percentage: natural graphite powder (laser particle size D 50 =65-90 μm) 52%, D374 composite powder 19%, medium temperature asphalt powder (softening point 100℃, coking value 65%) 12%, melamine 15% and SiC powder (laser particle size D 50 =65-90 μm) 2%.
[0040] Example 5 A porous natural graphite brush material, which differs from Example 1 only in the dry powder composition.
[0041] The dry powder consists of the following components by weight percentage: natural graphite powder (laser particle size D 50 =65-90 μm) 52%, D374 composite powder 19%, medium temperature asphalt powder (softening point 100℃, coking value 65%) 18%, melamine 9% and SiC powder (laser particle size D 50 =65-90 μm) 2%.
[0042] Example 6 A porous natural graphite brush material, which differs from Example 1 only in the dry powder composition.
[0043] The dry powder consists of the following components by weight percentage: natural graphite powder (laser particle size D 50 =65-90 μm) 52%, D374 composite powder 19%, medium temperature asphalt powder (softening point 100℃, coking value 65%) 15%, melamine 10% and SiC powder (laser particle size D 50 =65-90 μm) 4%.
[0044] Example 7 A porous natural graphite brush material, which differs from Example 1 only in the dry powder composition.
[0045] The dry powder consists of the following components by weight percentage: natural graphite powder (laser particle size D 50 =65-90 μm) 57%, D374 composite powder 14%, medium temperature asphalt powder (softening point 150℃, coking value 65%) 15%, melamine 12% and SiC powder (laser particle size D 50 =65-90 μm) 2%.
[0046] Comparative Example 1 Compared with Example 1, the only difference is the laser particle size D of natural graphite powder. 50 =40-60 μm.
[0047] Comparative Example 2 Compared with Example 1, the only difference is the laser particle size D of natural graphite powder. 50 =95-130 μm.
[0048] Comparative Example 3 Compared with Example 1, the only difference is that melamine is replaced by ammonium bicarbonate.
[0049] Comparative Example 4 Compared with Example 1, the only difference is that the organic solvent acetone is replaced by benzene.
[0050] Comparative Example 5 Compared with Example 1, the only difference is that the dry powder composition is different, as follows: The dry powder consists of the following components by weight percentage: natural graphite powder (laser particle size D 50 =65-90 μm) 35.5%, D374 composite powder 35.5%, medium temperature asphalt powder (softening point 100℃, coking value 65%) 12%, melamine 15% and SiC powder (laser particle size D 50 =65-90 μm) 2%.
[0051] Comparative Example 6 Compared with Example 1, the only difference is that step (1) does not involve heating and mixing, as follows: A porous natural graphite brush material, the preparation method is as follows: (1) Weigh natural graphite powder (laser particle size D 50 =65-90 μm) 52%, D374 composite powder 19%, medium temperature asphalt powder (softening point 100℃, coking value 65%) 15%, melamine 12% and SiC powder (laser particle size D 50 = 65-90 μm) 2%, stirred at 42 rpm for 3 h in a Z-type mixing pot to obtain dry powder; (2) Add plasticizer to the dry powder (calculated by weight percentage of dry powder, the plasticizer consists of 7.5% phenolic resin, 7.5% epoxy resin, 35% acetone and 50% alcohol), mix at 40 rpm for 1 hour, heat to 100°C, dry, cool naturally, and pass through a 200-mesh sieve. Pour it into a mold for pressing, use a 200-ton hydraulic press, set the pressure to 10 MPa, press and form, the green sheet specifications are 67×117×height dimension H, and the green sheet volume density is 1.5 g / cm 3 The compact was placed in a stainless steel crucible, compressed with fillers, sealed with refractory clay, and placed in a box furnace for roasting. The roasting temperature curve is shown in Table 1. After the roasting, it was naturally cooled to room temperature to obtain the product.
[0052] Test Case The performance indexes of the porous natural graphite brush materials prepared in Examples 1-7 and Comparative Examples 1-6 were tested respectively, and the specific testing methods are as follows: The pressing cracks and baking cracks are visually inspected, and the pressing qualified rate and baking qualified rate are calculated as follows: Compressing qualified rate (%) = qualified green sheets number ÷ total number of green sheets number × 100%; Roasting qualified rate (%) = number of qualified roasted products ÷ total number of roasted products submitted for inspection × 100%.
[0053] Resistivity (μΩ·m): in accordance with JB / T 8133.2.
[0054] Rockwell hardness: in accordance with JB / T 8133.3.
[0055] Flexural strength (MPa): in accordance with JB / T 8133.7.
[0056] Friction coefficient: in accordance with HB5367.10-1986.
[0057] Bulk density (g / cm 3 ): In accordance with JB / T 8133.14.
[0058] Porosity (%): in accordance with JB / T 8133.15.
[0059] The performance test results are shown in Table 2. It can be seen from Table 2 that by comparing Example 1 with Comparative Examples 1-6, it can be found that: 50 =65-90 μm natural graphite powder produced by the brush material has moderate wear resistance, will not wear the slip ring due to high hardness during operation, nor will it be easily broken due to low flexural strength; the resistivity and flexural strength are both optimal, which can ensure that the temperature rise of the brush is low during operation, the oxide film is easy to form, the oxide film thickness and balance ability are good, and the ability to suppress sparks is strong; the densely distributed connecting pores in the brush body can effectively balance the "air cushion" phenomenon generated when the brush faces the high-speed running slip ring, reducing arcs and sparks.
[0060] Table 2 Performance indicators
[0061] Finally, it should be noted that the above content is only used to illustrate the technical solution of the present invention, rather than to limit the scope of protection of the present invention. Simple modifications or equivalent substitutions of the technical solution of the present invention by ordinary technicians in this field do not deviate from the essence and scope of the technical solution of the present invention.
Claims
1. A method for preparing a porous natural graphite brush material, characterized in that: The steps include: (1) Mixing natural graphite powder, D374 composite powder, medium temperature asphalt powder, melamine and SiC powder to obtain dry powder; (2) Add plasticizer to the dry powder, mix, and calcine to obtain the product.
2. The preparation method according to claim 1, characterized in that: The laser particle size D of the natural graphite powder 50 =65-90μm, the softening point of the medium temperature asphalt powder is ≤100°C, the coking value is 65-69%, and the laser particle size of the SiC powder is D 50 =3-7 μm.
3. The preparation method according to claim 1, characterized in that: In terms of weight percentage, the dry powder consists of 47-57% natural graphite powder, 14-24% D374 composite powder, 12-18% medium-temperature asphalt powder, 9-15% melamine and SiC powder to make up to 100%.
4. The preparation method according to claim 1, characterized in that: The mixing process in step (1) includes stirring at 35-45 rpm for 2-3 h, heating to 90-110°C for 1-2 h, and finally cooling. The mixing speed in step (2) is 30-50 rpm, the mixing time is 0.5-1.5 h, and after the mixing is completed, it needs to be heated to 90-100°C, dried, cooled and sieved through a 100-200 mesh screen.
5. The preparation method according to claim 1, characterized in that: The plasticizer in step (2) comprises phenolic resin, epoxy resin, organic solvent and alcohol, wherein the phenolic resin accounts for 5-10% by weight of the dry powder, the epoxy resin accounts for 5-10% by weight of the dry powder, the organic solvent accounts for 15-35% by weight of the dry powder, and the alcohol accounts for 50-75% by weight of the dry powder.
6. The preparation method according to claim 5, characterized in that: The organic solvent is acetone.
7. The preparation method according to claim 1, characterized in that: The step (2) requires pressing before calcination, the pressing pressure is 10-20 MPa, and the volume density of the pressed green body is 1.3-1.6 g / cm 3 The calcination temperature curve includes first heating to 280-320°C, keeping warm for 3-4 hours, and a heating rate of 55-65°C / h; then heating to 400-420°C, keeping warm for 3.5-4.5 hours, and a heating rate of 3-5°C / h; then heating to 500-540°C, keeping warm for 3.5-4.5 hours, and a heating rate of 2-3°C / h; finally heating to 970-990°C, keeping warm for 11-13 hours, and a heating rate of 4-15°C / h.
8. A porous natural graphite brush material, characterized in that: Prepared by the preparation method according to any one of claims 1 to 7.
9. The porous natural graphite brush material according to claim 8, characterized in that: The volume density of the porous natural graphite brush material is 1.25-1.40 g / cm 3 , resistivity ≤27 μΩ·m, flexural strength 7-16 MPa, friction coefficient <0.3, HR 10 / 196 Rockwell hardness value 48-78, open porosity 35-42%.
10. Use of the porous natural graphite brush material according to any one of claims 8 to 9 in a brush.
Citation Information
Patent Citations
Graphite brush and preparation method thereof
CN106025745A
Manufacturing process of composite material brush
CN108907205A
Metal electrographite brush with low cost and good performance and preparation method of metal electrographite brush
CN104882759A
Polylactic resin composition, molded product, and method for producing polylactic resin composition
CN105008459A
Preparation method for high-resistivity carbon black-based electrographite electric brush material
CN105130436A